From Dreamed Sex to Advertised Sex: Sexual Deals in Daily Press - Filomena Teixeira; Fernando M. Marques (Universidade Estadual Paulista Júlio de Mesquita Filho, 2014)
Media are becoming increasingly permeable to speeches that bring into play pornographization processes of the public space. The sex ads published in the daily press represent an important example of this phenomenon. By resorting to sex trade practices as positive, relaxing and pleasurable experiences, they embody a particular way of producing identities. The present study is of qualitative nature and aims to map the enunciation modes and persuasion strategies that characterize the sex ads in the daily press, thus questioning its place in the networks of meaning that make the gender. The corpus of analysis was created after a compilation of sex ads collected for a month from a national and a local Portuguese newspaper. The concept of ethos, projected by Maingueneau in his theory of discourse analysis was used as a resource. For the coding and categorization process, the software WebQDA was used. The study showed a high feminization of offers of sexual services, a predominance of imaginary scenes associated with male sex, the use of language referring to values and practices in the world of pornography and the use of stereotypes that reinforce gender inequality.